KONTRIBUSI CORPORATE SOCIAL RESPONSIBILITY TERHADAP CITRA PERUSAHAAN DI PT. SUPER UNGGAS JAYA - Pudyaningsih, A. Ratna; Hastari, Sri; Rofi’I, Achmad (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2017)
This study aims to analyze the contribution of Corporate Social Responsibility at PT. Super Unggas Jaya and to determine the dominant CSR variables affect the image of the company at PT. Super Poultry Jaya, which is measured by the indicators of CSR, namely the performance variables and variable social responsibility performance of the impact of the product. This study uses a quantitative research method with type research sample proportions (proportional sampling) by using primary data and secondary data, the population in this study is the youth Sukorejo ranging from citizen representatives RW.08 until RW.012, and as many as 50 people to be the study sample. These results indicate there is a contribution of independent variables on the dependent variable of 75%, by doing T test are variable (X1) with (Y) with the result tcount (8.280) > ttable (2.01174) with a probability value of 0.0000 < 0,05 same thing was also obtained by the variable (X2) that have a significant effect on the (Y) with the result tcount (6.555)> ttable (2.01174). From the test results T can also be concluded that the variable (X1) is more dominant than the variable X2, obtained from the beta in standartdized coefficient (0.612> 0.484) and also produced a correlation value in the variable performance of societal 45% and the correlation value variable performance responsibility responsible for 31% of the impact of the product. In F test are significantly and positively influence simultaneously between variables X1 and variable X2 to company image with a value of count (74.513) > table (3.20). Keywords: CSR, Social Performance, Performance Products Liability Of Impact